Genetic screen for factors mediating PIN polarization in gravistimulated Arabidopsis thaliana hypocotyls. (10th April 2019) - Rakusová, Hana; Han, Huibin; Valošek, Petr; Friml, Jiří
Summary: Gravitropism is an adaptive response that orients plant growth parallel to the gravity vector. Asymmetric distribution of the phytohormone auxin is a necessary prerequisite to the tropic bending both in roots and shoots. During hypocotyl gravitropic response, the PIN3 auxin transporter polarizes within gravity‐sensing cells to redirect intercellular auxin fluxes. First gravity‐induced PIN3 polarization to the bottom cell membranes leads to the auxin accumulation at the lower side of the organ, initiating bending and, later, auxin feedback‐mediated repolarization restores symmetric auxin distribution to terminate bending. Here, we performed a forward genetic screen to identify regulators of both PIN3 polarization events during gravitropic response. We searched for mutants with defective PIN3 polarizations based on easy‐to‐score morphological outputs of decreased or increased gravity‐induced hypocotyl bending. We identified the number of hypocotyl reduced bending ( hrb ) and hypocotyl hyperbending ( hhb ) mutants, revealing that reduced bending correlated typically with defective gravity‐induced PIN3 relocation whereas all analyzed hhb mutants showed defects in the second, auxin‐mediated PIN3 relocation. Next‐generation sequencing‐aided mutation mapping identified several candidate genes, including SCARECROW and ACTIN2, revealing roles of endodermis specification and actin cytoskeleton in the respective gravity‐ and auxin‐induced PIN polarization events. The hypocotyl gravitropism screen thus promises to provide novel insights into mechanisms underlying cell polarity and plant adaptive development. Significance Statement: Plant gravitropism involves two distinct cellular polarizations of PIN3 auxin transporter to redirect intercellular auxin fluxes for the bending response. Here we identified a number of Arabidopsis mutants defective specifically in the PIN3 polarization events, establishing that gravity‐induced polarization is required for bending initiation and auxin feedback‐mediated second polarization for its termination. Molecular analysis of selected mutants revealed a crucial role of SCARECROW‐mediated endodermis specification and actin cytoskeleton in these polarization events during gravitropism.